2012
DOI: 10.1016/j.newast.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of the eta carinae primary wind with a century old slow equatorial ejecta

Abstract: We argue that the asymmetric morphology of the blue and red shifted components of the outflow at hundreds of AU from the massive binary system η Carinae can be understood from the collision of the primary stellar wind with the slowly expanding dense equatorial gas. Recent high spatial observations of some forbidden lines, e.g. [Fe III] λ4659, reveal the outflowing gas within about one arcsecond (2300 AU) from η Car. The distribution of the blue and red shifted components are not symmetric about the center, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 53 publications
(142 reference statements)
1
12
0
Order By: Relevance
“…As can be seen in Figure 3, the freely flowing primary wind is diverted from its initial radial direction as it passes through the shock, and it flows around the cloud. In our interpretation of the velocity map (Soker & Kashi 2012b) the post-shock gas flowing away from (towards) us forms the red-shifted (blue-shifted) component. Because of the inclination by 42 • of the equatorial plane (the line from the center of the grid to the large WBE cloud in our model) to our line of sight the blue and red-shifted components are not symmetric, as we show in the next section.…”
Section: Wind-wbe Interactionmentioning
confidence: 76%
See 2 more Smart Citations
“…As can be seen in Figure 3, the freely flowing primary wind is diverted from its initial radial direction as it passes through the shock, and it flows around the cloud. In our interpretation of the velocity map (Soker & Kashi 2012b) the post-shock gas flowing away from (towards) us forms the red-shifted (blue-shifted) component. Because of the inclination by 42 • of the equatorial plane (the line from the center of the grid to the large WBE cloud in our model) to our line of sight the blue and red-shifted components are not symmetric, as we show in the next section.…”
Section: Wind-wbe Interactionmentioning
confidence: 76%
“…Hence, Soker & Kashi (2012b) claimed, the conclusion of that ω ≃ 90 • cannot account for the velocity map does not hold. Instead, Soker & Kashi (2012b) suggested that the contribution of the winds collision gas to the observed velocity structure at hundreds of AU is small. The main contribution to the asymmetric flow structure is of the freely expanding primary wind as it collides with the WBE.…”
Section: The Velocity Structure At Hundreds Of Aumentioning
confidence: 99%
See 1 more Smart Citation
“…In previous papers we have already presented arguments to show that absorption and emission lines (Kashi & Soker 2007, 2008, 2016a, the hydrogen column density toward the binary system as deduced from X-ray absorption (Kashi & Soker 2009a,b), emission from blobs around the binary system (Soker & Kashi 2012), and other observations, all support the orientation of ω ≃ 90 • , i.e., secondary away from us during most of the orbit and in front of the primary at periastron.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The interpretation we prefer with ω ≃ 90 • , comes from detailed analysis and modeling of a plethora of observations, including many absorption and emission lines from many parts of the binary system (primary, secondary, their winds, the colliding winds structure, and gas located further out of the kashi@ariel.ac.il soker@physics.technion.ac.il binary orbit; Kashi & Soker 2009a,b), observations of the hydrogen column density toward the binary system as deduced from X-ray absorption (Kashi & Soker 2009a,b), and emission from blobs in the vicinity of the binary system such as the Weigelt blobs environment (Soker & Kashi 2012). We discussed in length in our previous papers why we believe the conclusions in the works listed above that suggest an orientation of ω ≃ 240 • -270 • have severe flaws.…”
Section: Introcutionmentioning
confidence: 99%